2020
DOI: 10.3390/jimaging6050030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Image TIFF Format and JPEG Compression Level in the Accuracy of the 3D Model and Quality of the Orthophoto in UAV Photogrammetry

Abstract: The aim of this study is to evaluate the degradation of the accuracy and quality of the images in relation to the TIFF format and the different compression level of the JPEG format compared to the raw images acquired by UAV platform. Experiments were carried out using DJI Mavic 2 Pro and Hasselblad L1D-20c camera on three test sites. Post-processing of images was performed using software based on structure from motion and multi-view stereo approaches. The results show a slight influence of image format and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 27 publications
4
28
1
Order By: Relevance
“…Note that taking data in RAW (it is a format to store images without compression) format instead of jpg format (see Table 2 ) in both aerial and terrestrial photogrammetry is recommended [ 36 , 37 , 38 ]. We will have a considerable increase in the size of the files when obtaining them from the raw camera but during the processing we will be able to improve different aspects of the photography that will improve our results especially in low light situations.…”
Section: Developed Methodologymentioning
confidence: 99%
“…Note that taking data in RAW (it is a format to store images without compression) format instead of jpg format (see Table 2 ) in both aerial and terrestrial photogrammetry is recommended [ 36 , 37 , 38 ]. We will have a considerable increase in the size of the files when obtaining them from the raw camera but during the processing we will be able to improve different aspects of the photography that will improve our results especially in low light situations.…”
Section: Developed Methodologymentioning
confidence: 99%
“…Now, we have in total 40 TOF images and 40 HC images. Second, all the images are converted to grayscale images and stored in tiff format [12] using the compression lossless method. Third, histogram stretching (HS) was employed to enhance image contrast.…”
Section: Methodsmentioning
confidence: 99%
“…Step 1: we obtain Z p ½rðkÞ, p = 1, ⋯, P 1 . See Equation (12) Each enhanced dataset contains P 2 new images. See Equation (13).…”
Section: Stochastic Poolingmentioning
confidence: 99%
“…For image processing of UAS dataset, Agisoft Metashape (2018) software was used. Recent studies on the impact of the image format in the SfM/MVS environment have shown the importance of using raw image both from the point of view of geometric accuracy and from the point of view of the quality of the dense point cloud (Alfio et al, 2020); consequently, the images were processed in the raw format.…”
Section: Data Processing At Time T1mentioning
confidence: 99%